Evaluation of NEUROG1 methylation status in stool specimens in the advanced adenomas and colorectal cancer - Zhang,Lijin; Lin,Aiping; Lin,Jie; Chen,Juan; Chen,Mengshi; Yu,Xunbin; Wu,Yijuan; Wang,Tao; Lu,Yan; Ba,Zhaofen; Cheng,Xiaowei; Zhang,Tiantian; et al. (PeerJ, 2025)
Background To assess the status of NEUROG1 methylation in the advanced adenoma and colorectal cancer. Methods The NEUROG1 methylation in tissue and stool samples from patients with colorectal cancer (CRC), advanced adenoma (AA), and non-advanced adenoma (NAA) were evaluated using methylation-specific quantitative polymerase chain reaction (PCR). Results In tissue samples, the NEUROG1 methylation detection rates were 36% for CRC, 24% for NAA, and 88% for AA. In stool samples, the NEUROG1 methylation detection had a sensitivity of 63.46% for CRC with a positive predictive value (PPV) of 85.94%. The overall diagnostic specificity of the test for the NAA and the healthy control was 76.32%, with a negative predictive value (NPV) of 40.28%. Conclusion NEUROG1 methylation detection can potentially be used in the CRC and AA screening.
Keywords: Colorectal cancer; NEUROG1; Stool; DNA methylation; Diagnosis